ATTACK IN VOLLEYBALL: THE TECHNICAL - TACTICAL ACTIONS AND GAME READING (Fiep Bulletin - online, 2014)
On volleyball's several manifestations it's necessary the participant make the attack move with conscience and after a critic reading and analysis of game's situation. Recent literacy has been talking about this issue in an isolated and unlinked from the game way, without showing game reading elements and much less the opposition interactions that are established. Thesenew elements of volleyball teaching and learning emerge from the praxiologic knowledge by Pierre Parlebas, who for more than 30 years builds analysis instruments of the internal logic of games and sports. This article comes from a teaching project named"PRINCÍPIOS ORIENTADORES PARA O ENSINO DO VOLEIBOL", coordinated by professors João Francisco Magno Ribas and Mauro Cesar Ribeiro Baldicera that happened on the first semester/2005 and counted with the participation of physical education students. The aim of this project was to propose a glance on the teaching/learning process that builds a closest realityto the game and that considers game characteristics (cooperation/opposition), and that supports game readings in a way to anticipate game moves. The parameter used to this analysis is based on the game analysis elements from the motor praxiology, more precisely on the classification system and on the  universals. In this article we will show this group reflection relating to attack moves. At the first moment we will show the structure used. Following this, we will describe the attack move opposition and cooperation actions. After that, we will highlight the main attach techniques. The possibilities and the development of the process of decision are on the last part of this article. We finish it making some considerations about the study and development possibilities.
Keywords: Volleyball; Technical-Tactical Elements and Motor Praxiology praxeologie motrice